REINVENTING THE SUDETENLAND IN THE CZECH LIT-ERATURE AFTER 1989 - NÉMETH-VÍTOVÁ, Lenka (Porównania, 2015)
The article deals with the problem of brooding over the history of the Sudetenland in the new Czech literature: novels Grandhotel (2006) by Jaroslav Rudiš, Peníze pro Hitlera (Money for Hitler, 2006) by Radka Denemarková and Habermannův mlýn (Habermann´s mill, 2001) by Josef Urban. Writ-ers, by using inter alia mythologization, fictionalization and narration inspired by real history, are trying to restore the “polyphony of a memory” of the space. In literature on Sudetenland, temporality, continuity and memory significantly form that space, so that they are joined with the spaciality in one, indivisible unity.